Copper-based sliding materials

The CU-SN alloy with high-tin concentration areas and optional additives like graphite and SiC in sliding members addresses wear resistance issues, offering enhanced durability and lubricity.

JP7623416B2Active Publication Date: 2025-01-28DAIDO METAL IND CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023057733
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-03-31
Publication Date
2025-01-28
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Existing CU-SN alloys used in sliding members fail to provide adequate wear resistance, especially under high loads and changing load directions, and are unsuitable for applications with varying bearing shapes.

Method used

A sliding member with a CU-SN alloy containing 1.5 to 10.0% by mass of SN, a high-tin concentration area of 500 μm with 1.1 times the average SN concentration, and dispersed areas of 5 to 93 pieces/mm, optionally with solid lubricating particles like graphite and hard particles like SiC, enhances wear resistance.

Benefits of technology

The high-tin concentration areas provide improved wear resistance by supporting the load effectively, reducing wear even under varying conditions, while solid lubricants and hard particles further enhance durability and lubricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623416000008
    Figure 0007623416000008
  • Figure 0007623416000009
    Figure 0007623416000009
  • Figure 0007623416000001
    Figure 0007623416000001
Patent Text Reader

Abstract

To provide a sliding member including bearing alloy made of Cu-Sn alloy that has a novel structure capable of improving wear resistance.SOLUTION: The sliding member of the present invention includes a bearing alloy made of a Cu-Sn alloy, and in the Cu-Sn alloy, Sn is contained by 1.5 to 10.0 mass%, with the remainder being Cu and impurities, and when viewed in a cross section perpendicular to the sliding surface, the Sn concentration is 1.1 times or more higher than the average Sn concentration of the Cu-Sn alloy, there are dispersed high tin concentration regions with an area of 500 μm2 or more, and the number of high tin concentration regions is 5 to 93 per 1 mm2.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to a copper-based sliding member, and more particularly to a sliding member including a bearing alloy containing a Cu-Sn alloy. [Background technology]

[0002] Cu-Sn alloys are widely used as bearing alloys because of their high strength and excellent wear resistance. In recent years, with the increase in load on bearings due to the increase in engine power and the reduction in bearing area due to the miniaturization of engines, there is a demand for further improvement in the wear resistance of sliding materials. Conventional measures for improving wear resistance include those described in Patent Document 1 and Patent Document 2, for example.

[0003] Patent Document 1 discloses a copper alloy in which Ag, Sn, Sb, In, Mn, Fe, Bi, Zn, Ni and / or Cr are dissolved in a Cu matrix, and secondary phases of these elements are not substantially formed. These additive elements dissolved in the Cu matrix move to the lining surface in parallel with the generation of frictional heat and changes in the lining surface structure, and partially form a concentrated layer of the additive elements, which further reacts with sulfur-based additives in the lubricating oil to form sulfur-based compounds, and the additive elements react with oxygen in the lubricating oil to form oxygen-based compounds. These concentrated layers and sulfur-based compounds have excellent solid lubrication properties, excellent sliding properties even under high surface pressure, and have the effect of reducing the amount of wear.

[0004] The bearing alloy of the plain bearing of the patent document 2 is characterized in that the concentration of dispersed fine elements (for example Sn) decreases continuously from the top area of ​​the plain bearing alloy towards the parting face area. The area with a high proportion of Sn ensures a high load-bearing capacity of the sliding element.

[0005] However, in Patent Document 1, wear progresses before a layer of concentrated solid solution strengthening elements is formed, so the wear resistance is insufficient for applications involving a large amount of wear. In Patent Document 2, when considering only the top area that mainly receives the load, the top area that mainly receives the load only has the same wear resistance as other conventional technologies. Moreover, since the part with a low Sn concentration cannot be used as the main load area, it is not suitable for applications where the load direction changes or where the bearing is flat. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-249924 [Patent Document 2] JP 2000-27866 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a sliding member including a bearing alloy containing a Cu-Sn alloy, which has a new structure capable of improving wear resistance. [Means for solving the problem]

[0008] According to one aspect of the present invention, there is provided a sliding member having a sliding surface, comprising a bearing alloy containing a Cu-Sn alloy, the Cu-Sn alloy containing 1.5 to 10.0 mass % Sn with the remainder being Cu and impurities, the Cu-Sn alloy having a tin concentration that is 1.1 times or more higher than the average Sn concentration (hereinafter also referred to as the Sn component) of the Cu-Sn alloy when viewed in a cross section perpendicular to the sliding surface, and having an area of ​​500 μm 2 The high tin concentration regions are dispersed and the number of high tin concentration regions is 1 mm 2 The number of sliding members is from 5 to 93 per unit.

[0009] The Sn content of the Cu-Sn alloy is preferably 8.0 mass % or less, and more preferably 2.0 mass % or more. The Cu—Sn alloy may further contain either or both of 0 to 5.0 mass % Ni and 0 to 1.0 mass % P.

[0010] According to one specific example of the present invention, the area ratio of the high tin concentration region is 5 to 47% when viewed in a cross section perpendicular to the sliding surface.

[0011] According to one embodiment of the invention, the bearing alloy may further comprise either or both of solid lubricant particles and hard particles, the solid lubricant particles preferably comprising or being graphite particles, and the hard particles preferably comprising or being SiC particles.

[0012] According to another aspect of the present invention, there is provided a sliding member comprising a back metal layer and a bearing alloy layer on the back metal layer, the bearing alloy layer containing the above-mentioned bearing alloy.

[0013] According to one embodiment of the present invention, the sliding member is a sliding bearing.

[0014] According to another aspect of the present invention, there is provided a bearing device including the above-mentioned sliding member.

[0015] The invention and its many advantages will now be explained in more detail with reference to the accompanying schematic drawings, which show, by way of example, some non-limiting examples. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram illustrating an example of the configuration of a sliding member according to a specific example of the present invention. [Diagram 2] 1 is a cross-sectional view perpendicular to the sliding surface of a Cu-Sn alloy of a sliding member according to one embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The sliding member of the present invention relates to a sliding member having a Cu-Sn alloy as a bearing alloy. The sliding member is used in sliding bearings such as journal bearings and thrust bearings used in the bearing parts of internal combustion engines and automatic transmissions for passenger cars. For example, the sliding member can be a sliding bearing molded into a cylindrical shape in the journal bearing, or a sliding bearing formed by combining a pair of semi-cylindrical members into a cylindrical shape. For the thrust bearing, the sliding bearing can be a sliding bearing molded into an annular shape, or a sliding bearing formed by combining a pair of semi-annular members into an annular shape. However, the sliding member may have other shapes and can be used as a sliding member other than a sliding bearing. For example, it can be used as a flat-shaped sliding plate in the reciprocating sliding part of an industrial machine in a grease lubrication environment. The present invention also covers a bearing device including such a sliding member.

[0018] An example of the configuration of a slide member 1 according to one embodiment of the present invention will be described. With reference to Fig. 1, a bearing alloy layer 2 is provided on a back metal layer 4. However, the back metal layer 4 is an optional element, and there may be only the bearing alloy layer 2 without the back metal layer 4. The surface of the bearing alloy layer 2 becomes the sliding surface 3. Optionally, an overlay can be provided on the bearing alloy layer 2, and even in that case, the surface of the bearing alloy layer 2 will be referred to as the sliding surface 3 in this specification.

[0019] The back metal layer 4 can be provided in order to improve the strength of the sliding member 1. Although not particularly limited, the back metal layer 4 can be made of a metal plate such as steel, an Fe alloy, Cu, or a Cu alloy, and as an iron-based material, a plate material of a predetermined size made of an Fe alloy such as hypoeutectoid steel, austenitic stainless steel, or ferritic stainless steel is preferable.

[0020] Optionally, an overlay can be provided on bearing alloy layer 2. The overlay can be a known overlay made of metals such as Bi, Sn, Pb, Ag, etc., or alloys mainly made of these metals, or synthetic resins, for improving the conformability of the surface of the sliding layer, and the method for forming the overlay can be known.

[0021] Optionally, an intermediate layer may be provided between the back metal layer 4 and the bearing alloy layer 2. For example, by providing a porous metal layer or intermediate layer on the surface of the back metal layer, i.e., on the side that forms the interface with the bearing alloy layer, the bonding strength between the sliding layer and the back metal layer can be increased.

[0022] The bearing alloy layer includes a bearing alloy made of a Cu-Sn alloy. Fig. 2 shows a cross-sectional view of a slide member 1 according to one embodiment of the present invention. This cross-sectional view is taken along a plane perpendicular to the sliding surface. In Fig. 2, high tin concentration regions 6, in which the concentration of Sn is relatively high, are dispersed in a matrix 8 of a Cu-Sn alloy. The high tin concentration regions 6 are regions having an Sn concentration that is 1.1 times or more the average Sn concentration of the Cu-Sn alloy, and have an area of ​​500 µm 2 Even if the area has a Sn concentration of 1.1 times or more, it is defined as being 500 μm 2 If the number of high tin concentration regions 6 is less than 1 mm, they are not included in the high tin concentration region 6. 2 The range is 5 to 93 per serving. The term "average Sn concentration in the Cu-Sn alloy" refers to the average Sn concentration in the Cu-Sn alloy, since there is variation in the Sn concentration in the Cu-Sn alloy due to the presence of high tin concentration regions 6, etc. In the present invention, this value is considered to be equal to the Sn content of the Cu-Sn alloy.

[0023] The high tin concentration region 6, which has a relatively large Sn concentration, is relatively hard and has high wear resistance. When Sn is uniformly dissolved in the Cu-Sn alloy, the Cu-Sn alloy as a whole bears the load. However, even in the Cu-Sn alloy of the same composition, the relatively hard high tin concentration region 6 is dispersed in the relatively soft matrix 8, and the high tin concentration region 6 mainly supports the mating surface, making the surface as a whole less susceptible to wear. As a result, even with the same average Sn concentration, the wear resistance is improved compared to when Sn is uniformly dissolved in solid solution. And, regardless of the depth, the cross section perpendicular to the sliding surface has the above structure, that is, the high tin concentration region 6 exists in the depth direction as well, so that high wear resistance is maintained even if wear progresses.

[0024] In the Cu-Sn alloy of the sliding member of the present invention, it is preferable that Sn does not substantially form a secondary phase (intermetallic compound) by dissolving in Cu. The secondary phase (intermetallic compound) of Cu-Sn is hard but also very brittle (brittle), so it easily breaks and falls off, and the fallen pieces of the secondary phase get between the sliding surface and the counter surface, damaging the sliding surface and accelerating wear. For this reason, there is a risk that improvement in wear resistance will be hindered. Note that the term "substantially free of secondary phase" in a Cu-Sn alloy means that the secondary phase is not substantially present in a Cu-Sn alloy, and is defined as a phase having a thickness of 3 μm or less. 2 If there is no secondary phase with an area of ​​3 μm or more, it is considered to be "substantially absent." 2 Whether or not a secondary phase having an area of ​​100 times or more is present is confirmed using an electron microscope at a magnification of 100 times or more.

[0025] The Cu-Sn alloy contains 1.5 to 10.0% by mass of Sn, with the remainder being Cu and impurities. If the Sn content is less than 1.5% by mass, the hardness is not improved to the extent that wear resistance is obtained. To obtain the hardness that provides wear resistance, the minimum Sn content is more preferably 2.0% by mass. Furthermore, the minimum Sn content is more preferably 3.0% by mass. If the Sn content exceeds 10.0% by mass, there is a high possibility that a secondary phase of Cu-Sn will be formed. In order to reliably reduce the possibility of the secondary phase being formed, the maximum Sn content is more preferably 8.0% by mass. Furthermore, the maximum Sn content is more preferably 6.5% by mass.

[0026] The Cu-Sn alloy may further contain either or both of 0-5.0% by mass Ni and 0-1.0% by mass P. When these elements are contained within the above ranges, it is easy to increase the corrosion resistance and improve the sinterability. When 0-5.0% by mass Ni is added, the strength increases and the wear resistance can be improved. However, when more than 5.0% by mass Ni is added, the sintering temperature increases, leading to an increase in costs. When 0-1.0% by mass P is added, the sinterability improves, so the strength increases and the wear resistance can be improved. However, when more than 1.0% by mass P is added, the sintering proceeds too much, making it difficult to control.

[0027] The Cu-Sn alloy preferably has an area ratio of high tin concentration region 6 of 5 to 47% when viewed in a cross section perpendicular to sliding surface 3. When the area ratio of high tin concentration region 6 is 5% or more, the above-mentioned effects can be efficiently exhibited, and when it is 47% or less, the stability of the sintering process can be reliably ensured without impairing the strength of the bearing alloy layer, making it easier to obtain a bearing alloy layer with the desired wear resistance.

[0028] The high tin concentration region 6 has an area of ​​500 μm 2 Even in a region having an Sn content 1.1 times or more the Sn content of the Cu-Sn alloy, the area is 500 μm 2 If the area is less than this, it is not included in the high tin concentration region 6. This is because if the area is so small, the effect of supporting the load is weak and it does not contribute to improving the wear resistance.

[0029] In the Cu-Sn alloy of the present invention, the number of high tin concentration regions 6 is 1 mm 2 The number of high tin concentration regions 6 is 5 to 93 per mm 2 If there are less than 5 particles per square inch, the above effect cannot be achieved. If there are more than 93 particles per square inch, the tin concentration tends to become uniform and the area is 500 μm 2 This means that there is a high possibility that a high tin concentration region having a tin concentration of 1.1 times or more and mainly supporting the mating surface cannot be obtained. In addition, in order to manufacture a bearing alloy layer containing more than 93 atoms, it is necessary to further reduce the particle size of the copper-tin alloy powder during manufacturing. In this case, if the particle size of the copper-tin alloy powder is too small, Sn is likely to diffuse during the sintering process. As a result, it becomes impossible to stably control the degree of Sn diffusion during the sintering process, and it becomes impossible to stably create the high tin concentration region 6.

[0030] As a preferred specific example, the area ratio of the region where the Sn concentration is 1.2 times the Sn content of the Cu-Sn alloy (hereinafter referred to as "1.2 times threshold region") is 5 to 42%. More preferably, the area ratio of the region where the Sn concentration is 1.3 times threshold is 5 to 35%. Even more preferably, the area ratio of the region where the Sn concentration is 1.4 times threshold is 5 to 26%. With such a configuration, the above-mentioned effects are more easily obtained.

[0031] As a preferred example, the number of regions with a threshold value of 1.2 times is 5 to 84 / mm 2 More preferably, the number of regions with a threshold value of 1.3 times is 5 to 61 / mm 2 More preferably, the number of regions with a threshold value of 1.4 is 5 to 54 / mm 2 In such a configuration, the above-mentioned effect is more easily obtained.

[0032] Optionally, the bearing alloy layer 2 may further contain 0.1-12.0 mass % of one or more solid lubricant particles selected from, for example, MoS2, WS2, graphite, and h-BN. The solid lubricant preferably contains graphite. More preferably, the solid lubricant is graphite. The 0.1-12.0 mass % solid lubricant disperses in the Cu-Sn alloy matrix to enhance lubricity and further improve wear resistance. However, if the solid lubricant exceeds 12.0 mass %, sinterability may be impaired.

[0033] Optionally, the bearing alloy layer 2 may further contain 0.1-5.0 mass% of one or more hard particles selected from, for example, SiC, Al2O3, SiO2, AlN, Mo2C, WC, Fe2P, and Fe3P. The hard particles preferably contain SiC. More preferably, the hard particles are SiC. 0.1-5.0 mass% of the hard particles are dispersed in the matrix to further increase the wear resistance. However, if the hard particles exceed 5.0 mass%, the sinterability may be impaired.

[0034] Next, a method for producing the bearing alloy layer (Cu-Sn alloy) of the sliding member of the present invention will be described. This method includes the following steps. 1. Prepare a copper-tin alloy powder containing a specified amount of Sn and a pure copper powder. If either or both of Ni and P are to be optionally contained, use a copper powder containing these elements instead of the copper-tin alloy powder (in this case, it will also be referred to as "copper-tin alloy powder" hereinafter). 2. Weigh out the copper-tin alloy powder and pure copper powder so that the Sn content is a specified value (Sn is 1.5 to 10.0 mass %) (if Ni, P are optionally contained, the specified limit or less). 3. Mix the weighed amount of copper-tin alloy powder with the pure copper powder, optionally adding solid lubricant particles and / or hard particles. 4. The mixed powder is spread on a substrate, for example a back metal when a bearing alloy layer is formed on the back metal. 5. Sinter the scattered powder at 800℃ to 900℃ for 10 to 31 minutes. 6. The sintered body is rolled to a specified thickness. 7. The sintered body having the specified thickness is further sintered at 800°C to 900°C for 10 to 31 minutes.

[0035] Under the above sintering conditions, the Sn in the copper-tin alloy powder diffuses into the pure copper powder, but sintering is not performed until it is uniformly diffused throughout the entire alloy, and instead, a region with a relatively high Sn concentration is formed around the region that was previously the copper-tin alloy powder. By adjusting the particle size and Sn concentration of the copper-tin alloy powder and the sintering conditions within the above ranges, the area ratio and number of high tin concentration regions per unit area can be adjusted.

[0036] The Sn content of the copper-tin alloy powder used as the raw material is preferably 3 to 15 mass %, and the average particle size is preferably 10 to 75 μm. For example, it is possible to create a portion with a high Sn concentration by using pure tin powder instead of the copper-tin alloy powder, but since a brittle secondary phase is formed, the wear resistance may not improve.

[0037] Next, a method for measuring the high tin concentration region will be described. To identify the high tin concentration region 6, a cross section of the bearing alloy layer 2 perpendicular to the sliding surface 3 is subjected to surface analysis using SEM-EPMA, and a high tin concentration region having a tin concentration 1.1 times or more higher than the average Sn concentration of the Cu-Sn alloy is determined. An example of the measurement conditions is shown in Table 1. The map obtained by the surface analysis is displayed as a concentration using a calibration curve (standard conditions), and a median filter is applied to binarize it. Then, a 500 μm 2 The Sn-rich region with an area of ​​0.5 mm or more is identified as a high-tin region. The threshold for high-tin region analysis is 0.5 mm 2 This needs to be done in the above areas.

[0038] [Table 1] EXAMPLES

[0039] Each of the samples shown in Tables 4 to 6 was produced by the manufacturing method described above. Copper-tin alloy powder with an Sn content of 3 to 15 mass% and pure copper powder were mixed to obtain the composition shown in the table, and then scattered on a substrate. However, for Samples 24 and 25, Cu-12Sn-15Ni-3P alloy powder was used instead of the copper-tin alloy powder. Also, for Samples 27 to 29, Sample 31, and Sample 32, a predetermined amount of graphite powder and SiC powder were also mixed. A steel plate with a thickness of 2.2 mm was used as the substrate. The scattered powder was subjected to the first sintering, rolling, and second sintering to obtain a bearing alloy layer with a thickness of 0.9 mm. The sintering conditions for each sample are shown in Table 2. The number and area ratio of high tin concentration regions (regions having a Sn concentration 1.1 times the threshold, ie, 1.1 times or more the average Sn concentration) in the bearing alloy layer were measured by the measurement method described above. A wear test was carried out for each sample under the conditions shown in Table 3, and the amount of wear of the sample after the test was measured. The results are shown in Tables 4 to 6.

[0040] [Table 2]

[0041] [Table 3]

[0042] From the results shown in Table 4, the Cu-Sn alloy contains 1.5 to 10.0 mass% Sn, and the number of high tin concentration regions with a threshold value of 1.1 is 1 mm 2 It was found that Samples 1 to 23 of the examples of the present invention, which have 5 to 93 particles per square inch, had a reduced amount of wear in a wear test when compared with Samples 41 to 47 of the comparative examples, which do not have a high tin concentration region, at the same Sn concentration.

[0043] [Table 4]

[0044] In the examples of the present invention, Samples 24 and 25 contain 5.0% by mass of Ni and 1.0% by mass of P in addition to 4.0% by mass of Sn in the Cu-Sn alloy. Table 5 shows the wear amount of these samples in the wear test. Table 5 also shows the test results of Samples 13 and 20, which have the same Sn concentration, number of high concentration regions, and area ratio as Samples 24 and 25, respectively, but do not contain Ni and P. From the results shown in Table 5, it was found that the wear amount is reduced by adding Ni and P when the Sn concentration, number of high concentration regions, and area ratio are the same.

[0045] [Table 5]

[0046] Table 6 shows a comparison between Samples 26 to 29, 31, and 32, which are examples of the present invention in which the bearing alloy contains graphite and SiC in addition to a Cu-Sn alloy with 3.0 mass% Sn, and Samples 26 and 30, which do not contain graphite or SiC. The results shown in Table 6 show that the amount of wear in the wear test is reduced by including graphite and SiC.

[0047] [Table 6]

[0048] Table 7 shows a comparison of the wear amount between the sample of the present invention and a comparative example (without high-concentration regions) in which the average Sn concentration of the Cu-Sn alloy is the same. From Table 7, the number of high-concentration regions is 40 / mm 2 5 pieces / mm 2 It can be seen that the improvement in wear resistance is more excellent when the average Sn concentration is in the range of 2.0 mass % to 8.0 mass %, regardless of the number of high-concentration regions.

[0049] [Table 7] [Explanation of symbols]

[0050] 1 Sliding member 2 Bearing alloy layer 3. Sliding surface 4 Backing layer 6 High tin concentration region 8. Matrix

Claims

1. A sliding member having a sliding surface, the sliding member comprising a bearing alloy containing a Cu-Sn alloy, The Cu-Sn alloy contains 1.5 to 10.0 mass% Sn, with the remainder being Cu and impurities; When viewed in a cross section perpendicular to the sliding surface, The Sn concentration is 1.1 times or more the average mass% of Sn contained in the Cu-Sn alloy, and the area is 500 μm 2 The high tin concentration regions are dispersed and the number of the high tin concentration regions is 1 mm 2 A sliding member having 5 to 93 particles per unit area.

2. 2. The slide member according to claim 1, wherein an area ratio of the high tin concentration region is 5 to 47% when viewed in a cross section perpendicular to the slide surface.

3. 3. The sliding member according to claim 1, wherein the Cu-Sn alloy contains Sn in an amount of 8.0 mass % or less.

4. 3. The sliding member according to claim 1, wherein the Cu-Sn alloy contains 2.0 mass % or more of Sn.

5. 3. The slide member according to claim 1, wherein the Cu-Sn alloy further contains either or both of 5.0 mass % or less of Ni and 1.0 mass % or less of P.

6. The bearing alloy is one or more solid lubricant particles selected from MoS 2 , WS 2 , graphite, and h-BN; and One or more hard particles selected from SiC, Al 2 O 3 , SiO 2 , AlN, Mo 2 C, WC, Fe 2 P, and Fe 3 P 3. The sliding member according to claim 1 or 2, further comprising either one or both of the following:

7. 7. The sliding member according to claim 6, wherein said solid lubricant particles are graphite particles.

8. 7. The sliding member according to claim 6, wherein the hard particles are SiC particles.

9. 3. A sliding member according to claim 1, further comprising a back metal layer and a bearing alloy layer on the back metal layer, the bearing alloy layer containing the bearing alloy.

10. The sliding member according to claim 9 , wherein the sliding member is a plain bearing.

11. A bearing device comprising the sliding member according to claim 10.

Citation Information

Patent Citations

  • Phosphorus-tin-nickel-containing lead-free copper-based bearing (bearing bush) material and preparation method thereof

    CN108103349A

  • Highhstrength* highhoil content* sintered oillcontaining bearing

    JP1979131528A

  • Copper-base sintered alloy excellent in wear resistance at high temperature

    JP1992000335A

  • Sliding material

    JP1992088139A

  • Copper alloy and sliding bearing, excellent in seizure resistance

    JP1997249924A